Establishment and characterization of an MDCK cell line stably-transfected with chicken Abcb1 encoding P-glycoprotein. (June 2016) - Sun, Yong; Guo, Tingting; Guo, Dawei; Guo, Li; Chen, Li; Zhang, Yu; Wang, Liping
Abstract: Chicken P-glycoprotein (chP-gp), encoded by Abcb1, determines the bioavailability because of its effect on pharmacokinetics of various drugs. However, comprehensive studies on chP-gp are still limited. In this study, the chicken full-length cDNA was first successfully cloned and then stably expressed in MDCK cell line. The open reading frame of chicken Abcb1 consists of 3864 nucleotides, encoding for a 1287-amino acid protein. Sequence alignments analysis showed that chicken P-gp had high identities with the homologues of turkey (95%), human (72%), pig (72%), rat (71%) and cattle (68%). The efflux ratio of rhodamine123 (Rho123, a human P-gp substrate) in ch Abcb1 transfected MDCK cells was significantly higher than that in the wild type MDCK cell (6.24 vs 1.64, P  < 0.05), suggesting a good transporting function of chicken P-gp overexpressed in the transfected cell. Importantly, MDCK-ch Abcb1 cells, unlike Caco-2 cells, exhibited biphasic saturation kinetics in transporting Rho123. In conclusion, an MDCK cell line stably expressing ch Abcb1 was successfully established, which could provide a new cell model to screen its substrates and inhibitors and study the drug-drug interaction medicated via chicken P-gp. Highlights: The full length cDNA of chicken P-gp (chP-gp) was first successfully cloned and analyzed. An MDCK-chP-gp cell line was generated and its efflux function was evaluated. Chicken P-gp, unlike human P-gp, showed biphasic saturation kinetics for Rho123.